Pengaruh Persepsi Penggunaan E-Filing Terhadap Kepatuhan Pelaporan SPT Tahunan Orang Pribadi Pada PT X - Hilmy Dwi Ismiranti (Jurnal Akuntansi Keuangan dan Bisnis, 2024)
This study aims to compare perceptions of the use of e-filing based on generational differences and its influence on compliance with reporting individual annual tax returns. Because the use of e-filing still requires teaching to use it for Taxpayers. Technology acceptance is based on two aspects according to TAM, namely perceived convenience and perceived usefulness which are independent variables in this research. Compliance with reporting individual annual tax returns is the dependent variable. The generations studied include generation The research results show that perceived convenience has a significant effect on reporting compliance with individual annual tax returns. Perception of usefulness has a significant effect on reporting compliance with Individual Annual Tax Returns. The generation of e-filing users has a significant influence on user perceptions of reporting compliance with Individual Annual Tax Returns. Perceived convenience and perceived usefulness simultaneously have a significant effect on reporting compliance with Individual Annual Tax Returns. This study aims to compare perceptions of the use of e-filing based on generational differences and its influence on compliance with reporting individual annual tax returns. Because the use of e-filing still requires teaching to use it for Taxpayers. Technology acceptance is based on two aspects according to TAM, namely perceived convenience and perceived usefulness which are independent variables in this research. Compliance with reporting individual annual tax returns is the dependent variable. The generations studied include generation The research results show that perceived convenience has a significant effect on reporting compliance with individual annual tax returns. Perception of usefulness has a significant effect on reporting compliance with Individual Annual Tax Returns. The generation of e-filing users has a significant influence on user perceptions of reporting compliance with Individual Annual Tax Returns. Perceived convenience and perceived usefulness simultaneously have a significant effect on reporting compliance with Individual Annual Tax Returns.